Method for judging stability of matrix asphalt oil source
By converting the component information of matrix asphalt into fluorescence brightness and phase state parameters, combining the fluorescence brightness and the phase state of polymer modified asphalt as a joint judgment basis, the problem of low efficiency in determining the stability of matrix asphalt in the prior art is solved, and fast and accurate oil source stability detection is achieved.
Patent Information
- Application Number
- CN202411640129.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to quickly and effectively determine the stability of the matrix asphalt oil source, resulting in low detection efficiency and large errors, making it difficult to identify unstable asphalt products.
By converting the component information of the matrix asphalt into fluorescence brightness and phase state parameters, combining the fluorescence brightness and the phase state of polymer modified asphalt as a joint judgment basis, a comprehensive determination of the stability of the matrix asphalt oil source is carried out.
Fast and effective oil source stability judgment has been achieved, the test cycle has been shortened to 1 minute to 30 minutes, the detection efficiency has been improved by nearly 300-10,000 times, and the accuracy and stability have been significantly improved.
Smart Images

Figure CN119595601A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt oil source determination, in particular to a method for determining the stability of a base asphalt oil source. Background Art
[0002] Matrix asphalt is one of the most important bulk construction materials in the field of road engineering. It is most widely used in asphalt pavements. Its performance directly determines the performance and service quality of asphalt pavements. The source of matrix asphalt oil is the most important factor in determining the application performance of matrix asphalt. Therefore, the stability of the oil source has a critical impact on the stability of the road quality of matrix asphalt.
[0003] There are many oil sources in the production of petroleum asphalt, and the raw materials are highly variable. There are many asphalt manufacturers. The production has changed from being dominated by main refineries to being dominated by local independent refineries. This has greatly increased the complexity of the quality of petroleum asphalt products. Asphalt that is filled and blended often appears in the market. Due to the disconnection between the current conventional testing indicators and road performance, as well as the low testing efficiency, these problematic asphalts are difficult to identify and discover, causing serious road quality problems.
[0004] Currently, there are two methods generally used to determine the stability of oil sources. One is the four-component method, which can directly reflect the differences in asphalt oil sources and has a clear test method, but the test cycle is long (the test time is as long as 7 days), the detection efficiency is extremely low, and the test repeatability is poor, the error is large, the operation requirements are high, and the current popularity is low; the other method is to use infrared spectroscopy to determine the stability of the oil source by measuring the similarity of the broad spectrum or fingerprint region group spectral information (usually with 95% similarity as the threshold). This method is simple and efficient, but in fact, because the group information of different types of asphalt is extremely similar or even consistent, this leads to the use of spectral analysis. Even different asphalt products are often identified as the same oil source, which is very error-prone.
[0005] Therefore, how to quickly and comprehensively determine the oil source stability of matrix asphalt and improve detection efficiency and detection stability is a technical problem that needs to be solved urgently. Summary of the invention
[0006] The technical task of the present invention is to provide a method for determining the stability of the oil source of matrix asphalt to solve the problem of how to quickly and comprehensively determine the stability of the oil source of matrix asphalt and improve the detection efficiency and detection stability.
[0007] The technical task of the present invention is achieved in the following way: a method for determining the oil source stability of base asphalt, which converts the component information of base asphalt into fluorescence brightness and phase state parameters, and uses the fluorescence brightness of base asphalt and the phase state of polymer-modified asphalt as a joint determination basis to comprehensively determine the oil source stability of base asphalt; the details are as follows:
[0008] S1. Determine the fluorescence brightness of the matrix asphalt: perform image processing on the matrix asphalt sample image, extract the gray value of the matrix asphalt observation sample, and compare the deviation between the gray value of the matrix asphalt observation sample and the gray value of the standard sample:
[0009] ① If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by more than the set threshold, it means that the oil source is greatly different;
[0010] ② If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by less than the set threshold, step S2 is executed;
[0011] S2. Determine the fluorescence phase state of polymer modified asphalt and determine the oil source stability based on the swelling degree.
[0012] Preferably, the determination of the fluorescence brightness of the matrix asphalt in step S1 is specifically as follows:
[0013] S101, melting asphalt, heating the base asphalt to 155-160°C;
[0014] S102, drop the matrix asphalt on the carrier, cool it to room temperature for 1-2 minutes, add a cover glass, and obtain a matrix asphalt observation sample;
[0015] S103, performing fluorescence observation on the matrix asphalt observation sample and taking pictures to obtain pictures of the matrix asphalt observation sample;
[0016] S104, graying the matrix asphalt observation sample image to extract the gray value of the matrix asphalt observation sample;
[0017] S105. Compare the gray value of the matrix asphalt observation sample with the gray value of the standard sample:
[0018] ① If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by more than 5%, it is considered that the oil source difference is large;
[0019] ② If the gray value of the observed sample of base asphalt deviates from the gray value of the standard sample by less than 3%, polymer modified asphalt is prepared and the oil source stability is determined in combination with the degree of swelling.
[0020] More preferably, when performing fluorescence observation on the matrix asphalt observation sample in step S103, the fluorescence exposure time used is 2999.9, the laser light source is blue, the wavelength range is 420-490nm, and the observation magnification is 400 times.
[0021] Preferably, the fluorescent phase state of the polymer modified asphalt is determined in step S2 as follows:
[0022] S201, melt the asphalt, heat the base asphalt to 155-160°C, weigh 500g for later use;
[0023] S202, adding SBS modifier to base asphalt, shearing with a high-speed shearing machine, and shearing at 160-170° C. for 10-20 min at a rotation speed of 1500-2000 rpm to obtain modified asphalt;
[0024] S203, adding a stabilizer to the modified asphalt, and obtaining a fluorescence observation sample of the modified asphalt after 15 minutes;
[0025] S204, observing the phase state of the modified asphalt fluorescence observation sample, and taking a picture to obtain a picture of the modified asphalt fluorescence observation sample;
[0026] S205, calculating the average particle size value of the developed particles according to the modified asphalt fluorescence observation sample;
[0027] S206. Compare the deviation between the average particle size value of the modified asphalt fluorescence observation sample and the particle size value of the standard sample:
[0028] ① If the average particle size of the modified asphalt fluorescence observation sample deviates by more than 5% from the particle size of the standard sample, it means that the oil source has a large variation;
[0029] ② If the average particle size of the modified asphalt fluorescence observation sample deviates from the particle size of the standard sample by no more than 5%, it indicates that the oil source is stable.
[0030] Preferably, the SBS modifier is a linear or star modifier for road use, such as 791, 1301, 161B, etc.
[0031] More preferably, the amount of SBS modifier added is 4.2-4.8% of the total amount of base asphalt.
[0032] Preferably, a single-value sulfur stabilizer is selected as the stabilizer, and the amount of the stabilizer added is 0.5‰-1.5‰ of the total amount of the modified base asphalt.
[0033] Preferably, in step S205, the average particle size of the developed particles is calculated based on the modified asphalt fluorescence observation sample as follows:
[0034] S20501. Prepare modified asphalt fluorescence observation samples, with two parallel test samples for each modified asphalt, and collect images of each modified asphalt fluorescence observation sample at at least three different locations;
[0035] S20502. Use Imagej software to calculate the particle size of the modified asphalt fluorescence observation sample image, and take the average value of the connected domain particle size as the characterization parameter;
[0036] S20503. After the particle size determination of all modified asphalt fluorescence observation sample images is completed, the average particle size value of the connected domain is calculated.
[0037] The method for determining the stability of the base asphalt oil source of the present invention has the following advantages:
[0038] (1) The test cycle of the present invention is only 1min-30min, which is 300-10000 times higher than the 7-day test time of the traditional four-component method. The test efficiency is greatly improved, and the oil source stability of asphalt can be identified at a faster speed. It has a guiding significance for limiting engineering applications and factory modified asphalt, avoiding the use of unstable samples in production and application, and preventing the occurrence of phenomena such as sequential filling;
[0039] (ii) The equipment used in the engineering laboratory during the determination process of the present invention are all general equipment with low prices, and the relevant materials used are all general materials in the market with high popularity and easy to obtain;
[0040] (3) The present invention has been verified by a large number of experiments and conforms to general rules, is not targeted at a specific matrix asphalt, has a wide range of applications, is highly practical, and has high application value;
[0041] (iv) In the process of determining the fluorescence phase of polymer modified asphalt, after adding the SBS modifier, the stabilizer is added to evenly distribute the polymer modifier in the asphalt, so as to ensure that the identification error caused by uneven sampling is eliminated during sampling; if the stabilizer is not added, the SBS modifier is mostly distributed in the matrix asphalt in the form of a single particle, which is easy to cause uneven sampling and affect the observation results;
[0042] (V) The present invention compares the average particle size value of the modified asphalt fluorescence observation sample obtained with the particle size value of the standard sample, thereby improving the accuracy of the measurement and effectively avoiding the problem of inaccurate determination results caused by single sampling. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The present invention is further described below in conjunction with the accompanying drawings.
[0044] Attached Figure 1 The flowchart of the method for determining the stability of the base asphalt oil source is shown;
[0045] Attached Figure 2This is the original fluorescence image of the standard sample;
[0046] Attached Figure 3 is the grayscale image of the standard sample (the grayscale value is 42.0);
[0047] Attached Figure 4 This is the original fluorescence image of sample 1;
[0048] Attached Figure 5 This is the grayscale image of sample 1 (the grayscale value is 46.4);
[0049] Attached Figure 6 This is the original fluorescence image of sample 2;
[0050] Attached Figure 7 This is the grayscale image of sample 2 (the grayscale value is 42.3);
[0051] Attached Figure 8 is the phase diagram with the standard sample;
[0052] Attached Fig. 9 is the phase diagram of sample 2;
[0053] Attached Fig.10 This is the original fluorescence image of sample 3;
[0054] Attached Fig.11 This is the grayscale image of sample 3 (the grayscale value is 42.6);
[0055] Attached Fig.12 This is the phase diagram of sample 3. DETAILED DESCRIPTION
[0056] The method for determining the stability of the base asphalt oil source of the present invention is described in detail below with reference to the accompanying drawings and specific examples of the specification.
[0057] Example:
[0058] The composition of matrix asphalt components clearly defines the oil source characteristics, and fluorescence reflects the composition of asphalt components. According to the petroleum and natural gas industry standard SY5614 and relevant literature, fluorescence microscopes can be used to observe coal seams, natural asphalt, asphalt substances in fine cracks and other organic rocks, and establish standards for determining asphalt components, content and properties. For example, the luminescent color reflects the composition of asphalt, the brightness reflects the content of asphalt, etc. The relationship between color and component is shown in Table 1.
[0059] Table 1 Asphalt components and fluorescent colors
[0060]
[0061] As can be seen from Table 1, the fluorescence colors emitted by different components are different. Fluorescence observation can quickly obtain certain asphalt component information.
[0062] The swelling development effect of polymer modified asphalt is closely related to the components of base asphalt. The components of asphalt are directly related to swelling. The fluorescence phase can reflect the component composition of asphalt, that is, the fluorescence phase of polymer modified asphalt also directly reflects the oil source characteristics of base asphalt.
[0063] As attached Figure 1 As shown, this embodiment provides a method for determining the oil source stability of base asphalt, which converts the component information of base asphalt into fluorescence brightness and phase state parameters, and uses the fluorescence brightness of base asphalt and the phase state of polymer-modified asphalt as a joint determination basis to comprehensively determine the oil source stability of base asphalt; the details are as follows:
[0064] S1. Determine the fluorescence brightness of the matrix asphalt: perform image processing on the matrix asphalt sample image, extract the gray value of the matrix asphalt observation sample, and compare the deviation between the gray value of the matrix asphalt observation sample and the gray value of the standard sample:
[0065] ① If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by more than the set threshold, it means that the oil source is greatly different;
[0066] ② If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by less than the set threshold, step S2 is executed;
[0067] S2. Determine the fluorescence phase state of polymer modified asphalt and determine the oil source stability based on the swelling degree.
[0068] The specific determination of the fluorescence brightness of the matrix asphalt in step S1 of this embodiment is as follows:
[0069] S101, melting the asphalt, heating the base asphalt;
[0070] S102, dropping the matrix asphalt on the carrier, cooling it to room temperature for a period of time, adding a cover glass, and obtaining a matrix asphalt observation sample;
[0071] S103, performing fluorescence observation on the matrix asphalt observation sample and taking pictures to obtain the matrix asphalt observation sample pictures; wherein, when performing fluorescence observation on the matrix asphalt observation sample, the fluorescence exposure time used is 2999.9, the laser light source is blue, and the observation magnification is 400 times;
[0072] S104, graying the matrix asphalt observation sample image to extract the gray value of the matrix asphalt observation sample;
[0073] S105. Compare the gray value of the matrix asphalt observation sample with the gray value of the standard sample:
[0074] ① If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by more than 5%, it is considered that the oil source difference is large;
[0075] ② If the gray value of the observed sample of base asphalt deviates from the gray value of the standard sample by less than 3%, polymer modified asphalt is prepared and the oil source stability is determined in combination with the degree of swelling.
[0076] The sample 1, the sample 2 and the heating thermometer cooling time of the samples are prepared and obtained through steps S101 to S103 as shown in Table 2.
[0077] Table 2 Preparation and acquisition of the cooling time summary of the heating thermometers for samples 1, 2 and 3
[0078] Sample name Step S101 Heating temperature (°C) Step S102 Cooling time (min) Wavelength (nm) in step S103 Sample 1 155 1 420 Sample 2 158 1.5 455 Sample 3 160 2 490
[0079] The specific method for determining the fluorescent phase of polymer modified asphalt in step S2 of this embodiment is as follows:
[0080] S201, melt the asphalt, heat the base asphalt, weigh 500g for later use;
[0081] S202, adding SBS modifier to base asphalt, shearing with a high-speed shearing machine, and shearing for a period of time at a set temperature while setting a rotation speed to obtain modified asphalt;
[0082] S203, adding a monovalent sulfur stabilizer to the modified asphalt, and obtaining a fluorescence observation sample of the modified asphalt after 15 minutes;
[0083] S204, observing the phase state of the modified asphalt fluorescence observation sample, and taking a picture to obtain a picture of the modified asphalt fluorescence observation sample;
[0084] S205. Calculate the average particle size of the developed particles based on the modified asphalt fluorescence observation sample; the details are as follows:
[0085] S20501. Prepare modified asphalt fluorescence observation samples. Two parallel test samples are prepared for each modified asphalt. Images of each modified asphalt fluorescence observation sample are collected at three different locations.
[0086] S20502. Use Imagej software to calculate the particle size of the modified asphalt fluorescence observation sample image, and take the average value of the connected domain particle size as the characterization parameter;
[0087] S20503. After all the modified asphalt fluorescence observation sample images are measured for particle size, the average particle size value of the connected domain is calculated;
[0088] S206. Compare the deviation between the average particle size value of the modified asphalt fluorescence observation sample and the particle size value of the standard sample:
[0089] ① If the average particle size of the modified asphalt fluorescence observation sample deviates by more than 5% from the particle size of the standard sample, it means that the oil source has a large variation;
[0090] ② If the average particle size of the modified asphalt fluorescence observation sample deviates from the particle size of the standard sample by no more than 5%, it indicates that the oil source is stable.
[0091] The parameters of the sample 2 and the sample 3 prepared and obtained through step S201 to step S203 are shown in Table 3.
[0092] Table 3 Preparation and acquisition of sample 2 and sample heating thermometer cooling time summary
[0093]
[0094] Prepare sample 1, sample 2 and sample 3 respectively through steps S101 to S103, and take a photo to obtain sample 1 (as shown in the attached figure). Figure 4 Sample 2 (as shown in the attached Figure 6 as shown) and Sample 3 (as shown in Fig.10 According to the fluorescence original image of each sample, the fluorescence of sample 1 (as shown in the attached Figure 5 Sample 2 (as shown in the attached Figure 7 as shown) and Sample 3 (as shown in Fig.11 According to the grayscale values of samples 1, 2 and 3 and the grayscale values of the standard sample (as shown in the attached Figure 2 and 3 The fluorescence brightness deviation is calculated from the gray value of the sample (as shown), and the oil source stability of the sample is determined as follows:
[0095] Compared with the standard sample, the grayscale change rate of sample 1 reaches 10%, which is much larger than 5%. The oil source has undergone significant variation, that is, the oil source of sample 1 is unstable and the brightness difference is large.
[0096] Compared with the standard sample, the grayscale change rate of sample 2 reaches 4.7%, which is less than 5%. Therefore, it is necessary to determine the oil source in combination with the phase state of polymer-modified asphalt. Specifically, the phase state diagram of sample 2 is obtained through steps S201 to 203, as shown in the attached figure. Fig. 9 As shown in the figure, the phase particle size of sample 2 is calculated to be 4.373 μm. Figure 8 The phase particle size of the standard sample shown is 1.381μm. Compared with the standard sample, although the fluorescence intensity of the matrix asphalt of Sample 2 is consistent, the phase particle size of its polymer modified asphalt is extremely different under the same development state. Therefore, it is determined that the oil source of Sample 2 has undergone a great variation compared with the standard sample, that is, the oil source of Sample 2 is unstable, the difference in fluorescence brightness is small, and the difference in phase is large.
[0097] Compared with the standard sample, the grayscale change rate of sample 3 reaches 0.7%, which is less than 3%. It is necessary to combine the phase state of polymer modified asphalt to determine the oil source. Specifically, the phase state diagram of sample 3 is obtained through steps S201 to 206, as shown in the attached figure. Fig.12 As shown in the figure, the phase particle size of sample 3 is calculated to be 1.359 μm. Figure 8 The phase particle size of the standard sample shown is 1.381 μm. Compared with the standard sample, although the fluorescence intensity of the matrix asphalt is consistent, and the relative deviation of the phase particle size of the polymer modified asphalt is less than 5% under the same development state, it is determined that the oil source of sample three is stable compared with the standard sample, that is, the oil source of sample three is stable, and the difference in fluorescence brightness and phase state is less than 5%. The data is summarized in Table 4.
[0098] Table 4 Data summary of sample 1, sample 2, sample 3 and standard sample
[0099]
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for determining the stability of base asphalt oil source, characterized in that: The method is to convert the component information of the matrix asphalt into fluorescence brightness and phase state parameters, and use the fluorescence brightness of the matrix asphalt and the phase state of the polymer modified asphalt as a joint judgment basis to make a comprehensive judgment on the oil source stability of the matrix asphalt; the details are as follows: S1. Determine the fluorescence brightness of the matrix asphalt: perform image processing on the matrix asphalt sample image, extract the gray value of the matrix asphalt observation sample, and compare the deviation between the gray value of the matrix asphalt observation sample and the gray value of the standard sample: ① If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by more than the set threshold, it means that the oil source is greatly different; ② If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by less than the set threshold, step S2 is executed; S2. Determine the fluorescence phase state of polymer modified asphalt and determine the oil source stability based on the swelling degree.
2. The method for determining the stability of base asphalt oil source according to claim 1, characterized in that: The determination of the fluorescence brightness of the matrix asphalt in step S1 is specifically as follows: S101, melting asphalt, heating the base asphalt to 155-160°C; S102, drop the matrix asphalt on the carrier, cool it to room temperature for 1-2 minutes, add a cover glass, and obtain a matrix asphalt observation sample; S103, performing fluorescence observation on the matrix asphalt observation sample and taking pictures to obtain pictures of the matrix asphalt observation sample; S104, graying the matrix asphalt observation sample image to extract the gray value of the matrix asphalt observation sample; S105. Compare the gray value of the matrix asphalt observation sample with the gray value of the standard sample: ① If the gray value of the matrix asphalt observation sample deviates from the gray value of the standard sample by more than 5%, it is considered that the oil source difference is large; ② If the gray value of the observed sample of base asphalt deviates from the gray value of the standard sample by less than 3%, polymer modified asphalt is prepared and the oil source stability is determined in combination with the degree of swelling.
3. The method for determining the stability of base asphalt oil source according to claim 2, characterized in that: When the matrix asphalt observation sample is subjected to fluorescence observation in step S103, the fluorescence exposure time used is 2999.9, the laser light source is blue, the wavelength range is 420-490nm, and the observation magnification is 400 times.
4. The method for determining the stability of base asphalt oil source according to claim 1, characterized in that: The specific method for determining the fluorescent phase state of polymer modified asphalt in step S2 is as follows: S201, melt the asphalt, heat the base asphalt to 155-160°C, weigh 500g for later use; S202, adding SBS modifier to base asphalt, shearing with a high-speed shearing machine, and shearing at 160-170° C. for 10-20 min at a rotation speed of 1500-2000 rpm to obtain modified asphalt; S203, adding a stabilizer to the modified asphalt, and obtaining a fluorescence observation sample of the modified asphalt after 15 minutes; S204, observing the phase state of the modified asphalt fluorescence observation sample, and taking a picture to obtain a picture of the modified asphalt fluorescence observation sample; S205, calculating the average particle size value of the developed particles according to the modified asphalt fluorescence observation sample; S206. Compare the deviation between the average particle size value of the modified asphalt fluorescence observation sample and the particle size value of the standard sample: ① If the average particle size of the modified asphalt fluorescence observation sample deviates by more than 5% from the particle size of the standard sample, it means that the oil source has a large variation; ② If the average particle size of the modified asphalt fluorescence observation sample deviates from the particle size of the standard sample by no more than 5%, it indicates that the oil source is stable.
5. The method for determining the stability of base asphalt oil source according to claim 4, characterized in that: SBS modifiers are linear or star modifiers for roads.
6. The method for determining the stability of base asphalt oil source according to claim 4, characterized in that: The amount of SBS modifier added is 4.2-4.8% of the total amount of base asphalt.
7. The method for determining the stability of base asphalt oil source according to claim 4, characterized in that: The stabilizer used is a single-value sulfur stabilizer, and the amount of stabilizer added is 0.5‰-1.5‰ of the total amount of modified base asphalt.
8. The method for determining the stability of base asphalt oil source according to claim 4, characterized in that: In step S205, the average particle size value of the developed particles is calculated based on the modified asphalt fluorescence observation sample as follows: S20501. Prepare modified asphalt fluorescence observation samples, with two parallel test samples for each modified asphalt, and collect images of each modified asphalt fluorescence observation sample at at least three different locations; S20502. Use Imagej software to calculate the particle size of the modified asphalt fluorescence observation sample image, and take the average value of the connected domain particle size as the characterization parameter; S20503. After the particle size determination of all modified asphalt fluorescence observation sample images is completed, the average particle size value of the connected domain is calculated.
Citation Information
Cited By
Asphalt homology identification method and device based on infrared spectrum, electronic equipment and storage medium
CN121074445A